1998
DOI: 10.1002/(sici)1099-0496(199808)26:2<125::aid-ppul9>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation index and outcome in children with acute respiratory distress syndrome

Abstract: The purpose of this investigation was to determine the predictive value of the ventilation index (VI) in children with acute respiratory distress syndrome (ARDS). We performed a 10‐year retrospective chart review of children who were admitted to the Pediatric Intensive Care Unit with a diagnosis of ARDS. Acute respiratory distress syndrome was defined as acute onset of diffuse, bilateral pulmonary infiltrates of noncardiac origin, and severe hypoxemia, defined as the ratio of the arterial partial pressure of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 13 publications
3
23
0
2
Order By: Relevance
“…The correlation between mean VI and duration of mechanical ventilation is consistent with the findings of Paret et al [3], who demonstrated the prognostic value of VI for children with ARDS at days 3-5 after initiation of mechanical ventilation. Our results show that the mean VI during the first 24 h after initiation of mechanical ventilation corresponds with duration of mechanical ventilation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The correlation between mean VI and duration of mechanical ventilation is consistent with the findings of Paret et al [3], who demonstrated the prognostic value of VI for children with ARDS at days 3-5 after initiation of mechanical ventilation. Our results show that the mean VI during the first 24 h after initiation of mechanical ventilation corresponds with duration of mechanical ventilation.…”
Section: Discussionsupporting
confidence: 90%
“…VI was calculated every 8 h during the first 24 h of mechanical ventilation, starting 8 h after initiation of mechanical ventilation. VI was defined as the product of partial pressure of arterial CO 2 (mm Hg) ϫ peak airway pressure (cm H 2 O) ϫ respiratory rate (breaths per minute) divided by 1000 [3]. The mean VI was defined as the arithmetic mean of the VIs at 8, 16, and 24 h after initiation of mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…This has not been a consistent finding in the literature, however, with many studies showing no correlation between indexes of respiratory severity and mortality (20,22,30,41,42).…”
Section: Discussionmentioning
confidence: 71%
“…This is a low rate if compared with the 43% observed in adult patients with ARDS (compared pooled mortality over 72 studies) (20) and in other pediatric studies. It has been estimated that ARDS accounts for 1% to 4% of all pediatric intensive care unit admissions, approximately 8% to 10% of patients requiring MV (6,21), and ARDS has an estimated mortality between 20% and 75% (22)(23)(24)(25)(26)(27)(28)(29). We should consider that as many as 43% of children with ARDS in the PALISI study had a secondary diagnosis of bronchiolitis that has a low mortality rate (6,30).…”
Section: Discussionmentioning
confidence: 96%